Implementasi Cash Management System (CMS) Pada Kementerian Kesehatan Republik Indonesia - Susanti, Fithriyah; Kuswandi, Aos; Riau, Dwi Putranto (Sawala : Jurnal Administrasi Negara, 2023)
Cash Management System (CMS) is a service provided by banks for institutions or companies to be able to manage finances non-cash. This non-cash policy is something that has just been implemented within the Directorate General of Pharmaceuticals and Medical Devices. This study aims to determine the implementation of CMS using the McKinsey 7S model, and analysis of strategies with SWOT and QSPM to obtain the best alternative strategies to improve CMS implementation. The method used is descriptive qualitative using primary and secondary data. The results of the study reveal that CMS implementation has been going well, although system errors, transaction failures and third parties still cannot make non-cash payments. The best alternative strategy that can be applied to institutions is to prepare SOPs, improve the quality of financial human resources, and carry out regular CMS evaluations. Thus, the implementation of CMS Banking within the Directorate General of Pharmaceuticals and Medical Devices still needs to be refined by considering the results of alternative strategies so that CMS implementation can be better in realizing clean, transparent and accountable financial management.